Expert testimony on domestic violence: a discourse analysis - Hamilton, Melissa (Law and society: recent scholarship, 2009)
Feminist and social constructivist theories -- Critical discourse analysis in the law -- Expert witness discourse : the legal framework -- Expert witness discourse : constructing the battered woman -- The discourses of resistance